An Observational Study On Pharmaceutical Care Based On The Place Of Practice Of Pharmacists. - S, Malini; Jaykar, B; Mathews, Santhosh M (International Journal of Membrane Science and Technology, 2023)
Background: Clinical pharmacists are crucial in enhancing patient care and medication effectiveness, focusing on safety and effectiveness, as they founded pharmaceutical care to improve patient quality of life. Methodology: An observational study was conducted on 869 patients in the southern state of India, examining prescription drugs received from various pharmacies, including community pharmacies, pharmacies connected to private hospitals, government medical college hospitals, and government Primary Health Centres. A self-administered, standardized, closed-ended questionnaire was employed. The data was sorted and summarized. Results: The study examined the impact of pharmacists' pharmaceutical care on workplaces, finding that patients appreciated the pharmacy's location, amenities, cleanliness, and hygiene. However, their educational background was not impressive. While most of them were unaware of the quality of the prescriptions they received, there wasn't much discontent with the medications' availability. The pharmacists' counselling attitude and knowledge were impressive. Conclusion: The study highlights the importance of pharmacists in pharmaceutical treatment, revealing that patients consider factors such as location, amenities, staff education, and attitude when choosing a pharmacy. Despite doubts about the quality of pharmaceuticals, adequate drug availability was found. The study also highlights the significance of pharmacists' knowledge and demeanor in responsible drug use, highlighting the need for both physical and professional aspects in pharmacy operations.